Self-healing and shape-memory properties of polymeric materials cross-linked by hydrogen bonding and metal–ligand interactions. Issue 33 (25th July 2019) - Kobayashi, Yuichiro; Hirase, Tomohiro; Takashima, Yoshinori; Harada, Akira; Yamaguchi, Hiroyasu
Abstract : Polymeric materials were prepared by cross-linking them with two independent non-covalent interactions, namely hydrogen bonding and metal–ligand interactions. Abstract : Polymeric materials were prepared by cross-linking them with two independent non-covalent interactions, namely hydrogen bonding and metal–ligand interactions. The fracture energy of the resultant polymeric material is higher than that of the polymeric material without non-covalent interactions as well as that with one non-covalent interaction. Moreover, the prepared polymeric materials show self-healing and shape memory properties.